Knowledge Sharing Mahasiswa KKM Melalui Pemanfaatan Limbah Kertas Menjadi Kerajinan Tangan - Eka Indah Yuslistyari; Gina Ramayanti; Hany Azza Umama; Meassa Monikha Sari; Ade Agus Surya; Reza Sakti (Universitas Islam Nahdlatul Ulama Jepara, 2019)
Kuliah kerja masyarakat (KKM) years 2019 raised the subject of community empowerment through the development of creative economy. Most of student do not have enough knowledge in the determination of the work program to be applied in the community activities in the kuliah kerja masyarakat (KKM), no shortage of waste paper, the local currency must be entrepreneurs on college students in utilization of waste as yet there is no. Objectives of the activities devotion through knowledge sharing to students through the utilization of waste paper to become how to make handicrafts including providing knowledge and skills and to improve entrepreneurial interest through the use of waste paper to students. The importance of activites is knowledge sharing. Participants activities of are KKM students in kecamatan Cikeusal and kecamatan Ciomas. Activities started by observation this field to find the problems that arise implementation are the next stage of the preparation of materials and practice making handicrafts. The results are knowledge sharing that took place to students able to provide understanding as provisions in empowering community. Through the knowledge sharing, KKM students increase skill development have especially in any by elementary substance waste paper to handicrafts. The outer covering this activity is the product handicrafts with basic made waste paper that is tissue box